Uji Aktivitas Antidiabetes Kombinasi Esktrak Daun Kelor (Moringa oleifera L.) dan Daun Jambu Biji (Psidium guajava) Pada Tikus Putih Jantan Galur Wistar - Wahyuni, Arifah Sri; Haryati, Resti Dwi; Fadhilah , Arini (Journal of Pharmaceutical and Sciences, 2025)
Purpose: to test whether the combination of Moringa oleifera L. and guava (Psidium guajava) leaf extract has a better effect in reducing blood glucose levels compared to single extracts. Method: an experiment with a pre- and post-test with control group design. The samples were Moringa leaves, guava leaves with 30 Wistar rats divided into 6 groups. Normal control group, negative control group (Na CMC 1%), positive control group (glibenclamide 5 mg/kgBW), Moringa leaf extract group dose 100 mg/kgBW, guava leaf extract group dose 105 mg/kgBW, and a combination group of Moringa leaf extract with guava leaves. Data analysis used a computerized program using the Welch ANOVA and Post Hoc Games-Howell tests. Results: showed that all treatment groups significantly reduced blood glucose levels compared to negative controls (p<0.05), but the effect was not comparable to positive controls and was not significant with normal controls on day 21. The combination of EEDK and EEDJB did not provide a better effect than the single extract. Conclusion: This study shows that the single extract and the combination of moringa leaf and guava leaf extracts have antidiabetic activity, but the combination of moringa leaf and guava leaf extracts did not show a better effect.